Mechanistic Studies on the Photoaddition Reactions of Some 2-Cyclohexenones with Norbornadiene and Cyclopentene - Rasmussen, Paul W. (My University, 1969)
In order to gain mechanistic information of photoaddition reactions of 2-cyclohexenones, the additions of 2- and 3-methyl-2-cyclohexenone and 2-cyclohexenone to bicyclo[2.2.1]hepta-2,5-diene have been studied. Substituted 2-cyclohexenone products are obtained in addition to cyclobutane derivatives, and it is proposed that the former adducts arise from diradical intermediates and intramolecular hydrogen shifts. The photo-rearrangement, of 4, 4-dimethyl-2-cyclohexenone, and its photocycloaddition to cyclopentene, was studied in order to identify the enone excited state responsible for cycloaddition. These results, and naphthalene quenching experiments, indicate that all of the additions studied proceed via triplet excited states.
Keywords: mechanistic, photoaddition reactions, cyclohexenones, norbornadiene, cyclopentene, intramolecular, excited states